2014
DOI: 10.1038/npp.2014.265
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory Synaptic Function and Plasticity is Persistently Altered in Ventral Tegmental Area Dopamine Neurons after Prenatal Ethanol Exposure

Abstract: Prenatal ethanol exposure (PE) is one of the developmental factors leading to increased addiction propensity (risk). However, the neuronal mechanisms underlying this effect remain unknown. We examined whether increased excitatory synaptic transmission in ventral tegmental area (VTA) dopamine (DA) neurons, which is associated with drug addiction, was impacted by PE. Pregnant rats were exposed to ethanol (0 or 6 g/kg/day) via intragastric intubation from gestational day 8-20. Amphetamine self-administration, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 64 publications
3
35
0
Order By: Relevance
“…Likewise, increased sensitivity in the CPP, induced by a psychostimulant drug such as amphetamine, was observed in PAE rats upon reaching adulthood (Wang et al, ). Moreover, rats receiving alcohol during gestation self‐administered more amphetamine and exerted greater effort to obtain the drug under a PR schedule (Hausknecht et al, ; Wang et al, ). In contrast to our findings, increased locomotor sensitization to psychostimulants, such as cocaine and amphetamine, was described in adult PLAE offspring rats (Barbier et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, increased sensitivity in the CPP, induced by a psychostimulant drug such as amphetamine, was observed in PAE rats upon reaching adulthood (Wang et al, ). Moreover, rats receiving alcohol during gestation self‐administered more amphetamine and exerted greater effort to obtain the drug under a PR schedule (Hausknecht et al, ; Wang et al, ). In contrast to our findings, increased locomotor sensitization to psychostimulants, such as cocaine and amphetamine, was described in adult PLAE offspring rats (Barbier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, GluA2-lacking AMPARs in the NAc regulate the incubation of cocaine craving after prolonged withdrawal (Conrad et al, 2008). In an FASD rat model, Hausknecht et al (2015) reported a persistent augmentation of calcium-permeable AMPAR expression in VTA DA neurons, which could lead to an enhanced excitatory synaptic strength. Also, binge alcohol exposure during the third trimester-equivalent period to human pregnancy increased the frequency of spontaneous excitatory glutamatergic postsynaptic currents in the basolateral amygdala of offspring rats (Baculis, Diaz, & Fernando Valenzuela, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dopaminergic circuits encode or incentivize reward or reward-learning, 90 and a rich body of literature has shown that substance abuse alters dopaminergic neurotransmission. [91][92][93][94] Exposure to drugs of abuse, including morphine, ethanol, cocaine, or methamphetamine induces morphological, [95][96][97][98] electrophysiological, 38,99 biomolecular, 100,101 and plasticity 98,[102][103][104] changes in midbrain VTA dopaminergic neurons and their projections to the ventral striatum.…”
Section: Dopamergic Changes In Substance Use Disordersmentioning
confidence: 99%
“…However, patients exhibiting comorbidity between PTSD and alcohol use disorder also feature dysregulations of mesolimbic dopaminergic transmission (for review see Gilpin & Weiner, ). PAE also results in a dysregulated DA system (Converse et al, ; Schneider, Moore, & Adkins, ; Shen, Choong, & Thompson, ) due to abnormally increased excitatory synaptic strength in VTA DA neurons, which increases behavioral sensibility to drug abuse and increased addiction risk in PAE animals (Hausknecht et al, ).…”
Section: Discussionmentioning
confidence: 99%